Strengthening Youth Scientific Literacy on Local History and Culture Through Cultural Discussions in Aceh Barat Daya - ria ceriana; Hastuti Hastuti (CV Abid Abadi Jaya, 2026)
knowledge in the form of local culture and regional languages amidst the currents of modernization and technological development. The activity was carried out through a participatory and educational approach in the form of a cultural discussion forum organized by Aceh Culture and Education (Action) in Aceh Barat Daya. Participants included students, university students, cultural activists, academics, and community leaders. The methods used consisted of material presentations, interactive discussions, question-andanswer sessions, and participatory evaluations. The results showed that participants demonstrated high enthusiasm and gained a better understanding of the importance of preserving local culture as a regional identity, particularly in relation to scientific knowledge. In addition, the activity successfully created a collaborative space among communities and encouraged youth involvement in cultural preservation efforts. The cultural discussion forum became an effective educational medium for strengthening cultural literacy and developing the character of the younger generation based on local wisdom.